2012
DOI: 10.1105/tpc.112.096032
|View full text |Cite
|
Sign up to set email alerts
|

A Previously Unknown Oxalyl-CoA Synthetase Is Important for Oxalate Catabolism in Arabidopsis

Abstract: Oxalate is produced by several catabolic pathways in plants. The best characterized pathway for subsequent oxalate degradation is via oxalate oxidase, but some species, such as Arabidopsis thaliana, have no oxalate oxidase activity. Previously, an alternative pathway was proposed in which oxalyl-CoA synthetase (EC 6.2.1.8) catalyzes the first step, but no gene encoding this function has been found. Here, we identify ACYL-ACTIVATING ENZYME3 (AAE3; At3g48990) from Arabidopsis as a gene encoding oxalyl-CoA synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
158
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(170 citation statements)
references
References 69 publications
11
158
0
1
Order By: Relevance
“…In plants, various formate production pathways including photorespiration, glycolysis, cell wall synthesis, or degradation have been proposed (Igamberdiev et al, 1999;Hanson et al, 2000), but direct experimental evidence is limited. Recently, a previously unknown oxalyl-CoA synthetase, ACYL-ACTIVATING ENZYME3 (AAE3), was identified to be involved in oxalate degradation to form formate, which is further degraded by FDH in Arabidopsis (Foster et al, 2012). Furthermore, FDH is coexpressed with AAE3 and regulated by AAE3.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, various formate production pathways including photorespiration, glycolysis, cell wall synthesis, or degradation have been proposed (Igamberdiev et al, 1999;Hanson et al, 2000), but direct experimental evidence is limited. Recently, a previously unknown oxalyl-CoA synthetase, ACYL-ACTIVATING ENZYME3 (AAE3), was identified to be involved in oxalate degradation to form formate, which is further degraded by FDH in Arabidopsis (Foster et al, 2012). Furthermore, FDH is coexpressed with AAE3 and regulated by AAE3.…”
Section: Discussionmentioning
confidence: 99%
“…The proposition of another pathway for oxalate catabolism can date back to 1961 (Giovanelli and Tobin, 1961), but the enzyme has not been discovered until recently. Foster et al (2012) characterized Arabidopsis ACYL-ACTIVATING ENZYME3 (AAE3) gene encoding an oxalyl-CoA synthetase that is capable of catalyzing the first step in the CoA-dependent pathway of oxalate catabolism. To date, oxalate oxidase was found only in monocots but seems absent in dicots, but oxalyl-CoA synthetase was reported to exist in Arabidopsis (Foster et al, 2012), Medicago truncatula (Foster et al, 2016), and yeast (Saccharomyces cerevisiae ;Foster and Nakata, 2014).…”
mentioning
confidence: 99%
“…Foster et al (2012) characterized Arabidopsis ACYL-ACTIVATING ENZYME3 (AAE3) gene encoding an oxalyl-CoA synthetase that is capable of catalyzing the first step in the CoA-dependent pathway of oxalate catabolism. To date, oxalate oxidase was found only in monocots but seems absent in dicots, but oxalyl-CoA synthetase was reported to exist in Arabidopsis (Foster et al, 2012), Medicago truncatula (Foster et al, 2016), and yeast (Saccharomyces cerevisiae ;Foster and Nakata, 2014). While oxalate oxidase was found to be localized to the cell wall and oxalyl-CoA synthetase was localized in cytoplasm, both play a role in defending plants against oxalate-secreting fungal phytopathogens.…”
mentioning
confidence: 99%
“…14 To date, AAE3 proteins from rice bean, Medicago truncatula, and Arabidopsis (Arabidopsis thaliana) have been characterized as oxalyl-CoA synthetases. 13,15,16 Here, amino acid sequence alignment revealed that AAE3 proteins from common buckwheat and amaranth display high identity with known AAE3 proteins, all having a conserved AMP binding domain and acetylCoA synthetase domain (Fig. 2).…”
mentioning
confidence: 84%
“…Although the biochemical and molecular biological characterization of FeAAE3 and AhAAE3 proteins has to be investigated, it is reasonable to suggest that they also function as oxalyl-CoA synthetases. Given that AAE3 protein is characterized by having activities specific to oxalate, 13,15,16 the upregulation of AAE3 genes suggests that oxalate accumulates under Al stress.…”
mentioning
confidence: 99%